Bilateral Striatal Necrosis with Polyneuropathy with a Novel SLC25A19 (Mitochondrial Thiamine Pyrophosphate Carrier OMIMI*606521) Mutation: Treatable Thiamine Metabolic Disorder—A Report of Two Indian Cases - Gowda, Vykuntaraju K.; Srinivasan, Varunvenkat M.; Jehta, Kapil; Bhat, Maya D. (Neuropediatrics, 2019)
Background SLC25A19 gene mutations cause Amish congenital lethal microcephaly and bilateral striatal necrosis with polyneuropathy. We are reporting two cases of bilateral striatal necrosis with polyneuropathy due to SLC25A19 gene mutations.Methods A 36-month-old boy and a 5-year-old girl, unrelated, presented with recurrent episodes of flaccid paralysis and encephalopathy following nonspecific febrile illness. Examination showed dystonia and absent deep tendon reflexes.Results Nerve conduction studies showed an axonal polyneuropathy. Magnetic resonance imaging (MRI) of the brain in both cases showed signal changes in the basal ganglia. Next-generation sequencing revealed a novel homozygous missense variation c.910G>A (p.Glu304Lys) in the SLC25A19 gene in the boy and a homozygous mutation c.869T > A (p. Leu290Gln) in the SLC25A19 gene in the girl. Mutations were validated by Sanger sequencing, and carrier statuses of parents of both children were confirmed. Both children improved with thiamine supplementation.Conclusion If any child presents with recurrent encephalopathy with flaccid paralysis, dystonia, and neuropathy, a diagnosis of bilateral striatal necrosis with polyneuropathy due to SLC25A19 mutations should be considered and thiamine should be initiated.
Keywords: India; bilateral striatal necrosis; polyneuropathy; SLC25A19 gene